Push and Pull : Emerging Risks in Frontier Economy Access to International Capital Markets - Haque, Tobias; Bogoev, Jane; Smith, Greg (World Bank, Washington, DC, 2017)
Over the past decade, a large number of low- and lower-middle income ‘frontier economies’ have begun to access international private capital markets to meet fiscal financing needs. In this paper we seek to identify drivers of this trend, identify associated risks, and present policy implications for frontier-market policy-makers. Through simple analysis of the characteristics of recent frontier market issuers, we show that smaller, poorer, and less well-governed economies are now accessing global credit markets. Through cross-country regression analysis, however, we demonstrate that the capacity of these countries to issue debt (and the cost of this debt) continues to be influenced by their macroeconomic performance and quality of governance. Drawing on evidence from Ghana and Zambia, we illustrate potential risks arising from recent expansions of access to global debt markets, where rapid debt accumulation of foreign-denominated debt in the context of lessened market discipline and following recent debt relief is now posing pronounced debt sustainability and refinancing risks. We conclude that increased access to international debt markets presents both opportunities and risks to frontier issuers. The new cohort of frontier issuing economies should: i) take careful account of debt risks and debt sustainability considerations when developing fiscal policy and debt strategies; ii) work to reduce the costs of ongoing external borrowing through adopting sound economic policies and protecting credit ratings; and iii) develop domestic debt markets as a potential alternative source of fiscal financing through which to reduce reliance on foreign-denominated Eurobond debt with its associated refinancing and currency risks.